Employee Attitudes and Behavior in Improving Service Quality (Study: Café Navia Bangkalan) - Damayanti, Ira Alvina; Urjuan Mamduh; Fadjar Maulana; Iriani Ismail (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This article discusses employee attitudes and behavior in improving service quality in a business. This article aims to investigate the relationship between employee attitudes and behavior and improving service quality in an organizational context. Service quality has become a key factor in the success of various types of organizations, especially in the Navia cafe business. This research uses a survey method to collect data from employees who work at Cafe Navia. Data collected includes employees' attitudes toward their jobs, including job satisfaction, motivation, and engagement in their work. In addition, employee behavior related to service, such as responsiveness to customers, communication skills, and commitment to quality standards, is also evaluated. Based on the sources that have been collected, the results of this research are expected to provide better insight into how employee attitudes and behavior can influence the quality of services provided by the organization. This research can serve as a guide for managers and organizational leaders in developing strategies and policies aimed at improving service quality through managing employee attitudes and behavior